2016
DOI: 10.1021/acs.jpca.6b01278
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Red-Shifted Optical Spectra Recorded for Aza-BODIPY Dyes

Abstract: The optical properties are compared for two boron dipyrromethene (BODIPY) dyes that differ by virtue of the substituent at the meso-site, namely, aza-N versus C-methine atoms. Both compounds are equipped with aryl rings at the 3- and 5-positions of the dipyrrin backbone, which help to extend the degree of π-delocalization. The aza-BODIPY dye absorbs and fluoresces at much lower energy than does the conventional BODIPY dye, with red shifts of about 100 nm being observed in fluid solution, but with comparable fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 75 publications
2
47
0
Order By: Relevance
“…The sole replacement of the central meso carbon by an aza group entails a pronounced bathochromic shift of the spectral bands. The electronegative character of the nitrogen stabilizes the LUMO state (around 0.58 eV), whose electronic density is concentrated in such key meso position, lowering the energy gap (Figure ) . To push this shift even further towards the red edge of the visible region, the chromophoric backbone has been decorated with aromatic frameworks, bearing also electronic rich moieties (such as electron donor methoxy and electron acceptor trifluoromethyl), at positions 3 and 5, and 1 and 7 respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The sole replacement of the central meso carbon by an aza group entails a pronounced bathochromic shift of the spectral bands. The electronegative character of the nitrogen stabilizes the LUMO state (around 0.58 eV), whose electronic density is concentrated in such key meso position, lowering the energy gap (Figure ) . To push this shift even further towards the red edge of the visible region, the chromophoric backbone has been decorated with aromatic frameworks, bearing also electronic rich moieties (such as electron donor methoxy and electron acceptor trifluoromethyl), at positions 3 and 5, and 1 and 7 respectively.…”
Section: Resultssupporting
confidence: 93%
“…However, Harriman et al . suggested that, albeit the replacement of the methine carbon by an aza group affects the S 1 ‐T 1 energy gap, the intersystem crossing is ineffective in aza‐BODIPYs . They pinpoint that the sensitivity of the fluorescence deactivation with the solvent could be related to a specific interaction between hydrogen bonding solvents (i. e., alcohols) and the chromophoric aza group.…”
Section: Resultsmentioning
confidence: 99%
“…These molecules share structural similarities between them, such as the two azaBODIPY style structures (13 and 16) and the two TCNQesque structures (17 and 18), and in fact some azaBODIPY and TCNQ derivatives are thought to be SF active experimentally. [62,63] It is clear from the structures that the presence of a tetraradical character amongst predicted SF compounds is distributed across the chemical space and is not related to a specific chromophore e. g. there are other azaBODIPY derivatives within our dataset which do belong to the biradicaloid class. Since these are only a handful of suspicious entries in a set of 201 satisfactory molecules, the evidence for exothermic SF in a tetraradicaloid cannot be considered conclusive but should warrant further investigation, especially since all of them fall within the efficient SF energy range i. e. 0 < E(S 1 ) -2•E(T 1 ) < 0.5 eV.…”
Section: Resultsmentioning
confidence: 95%
“…The title compound BD was available from previous studies [17] and purified by column chromatography before use and its purity checked by NMR spectroscopy.Q uantum yields of fluorescence were measured by the comparison method using AzaBODIPY (5,5-difluoro-3,7bis(4-methoxyphenyl)-1,9-5H-4l4,5l4-dipyrrolo[1,2-c:2',1f[1,3,5,2]triazaborinine). [24] Selected data are shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%